Antimycobacterial neolignans isolated from Aristolochia taliscana - Rosalba León-Díaz; Mariana Meckes; Salvador Said-Fernández; Gloria Maria Molina-Salinas; Javier Vargas-Villarreal; Javier Torres; Julieta Luna-Herrera; Adelina Jiménez-Arellanes (Memorias do Instituto Oswaldo Cruz, 2010)
Tuberculosis (TB - Mycobacterium tuberculosis) is an ancient infectious disease that has appeared once again as a serious worldwide health problem and now comprises the second leading cause of death resulting from a single infection. The prevalence of multidrug resistance (MDR) TB is increasing and therapeutic options for treatment are not always accessible; in fact, some patients do not respond to the available drugs. Therefore, there is an urgent need to develop novel anti-TB agents. The aim of the present study was to screen extracts of Aristolochia taliscana, a plant used in traditional Mexican medicine to treat cough and snake bites, for antimycobacterial activity. The hexanic extract of A. taliscana was tested by microdilution alamar blue assay against Mycobacterium strains and bioguided fractionation led to the isolation of the neolignans licarin A, licarin B and eupomatenoid-7, all of which had antimycobacterial activity. Licarin A was the most active compound, with minimum inhibitory concentrations of 3.12-12.5 μg/mL against the following M. tuberculosis strains: H37Rv, four mono-resistant H37Rv variants and 12 clinical MDR isolates, as well as against five non-tuberculous mycobacteria (NTM) strains. In conclusion, licarin A represents a potentially active anti-TB agent to treat MDR M. tuberculosis and NTM strains.